Demand for Local Public Schooling: Another Brick in the Wall. - Åsa Ahlin; Eva Johansson (Uppsala University, Department of Economics, 2000)
In this paper we investigate the demand for local public school expenditures in Sweden. By using survey data, a method previously never applied to Swedish data, the paper provides an additional piece of evidence on individual demand for publicly provided local services. Estimating a linear demand specification, we find that the demand is inelastic with respect to income and tax, much in line with previous Swedish findings in a median voter framework. Estimation of a log-linear demand specification indicates more elastic demand. Testing the hypothesis that municipal employees tend to have a higher demand for public spending than others, we conclude that income, as well as taxprice, enters the demand function differently for the two groups of employees. We find no evidence of Tiebout sorting.
Keywords: C25; H40; H72; 330; Demand for local public school expenditure; survey data; public employees; Schulfinanzierung; Schweden